A Hybrid Fuzzy Model for the performance evaluation of Biomethane gas as a renewable energy source - Aikhuele, Daniel O.; Akinosi, Olatunji A.; Faiz, Mohd Turan (Springer, 2021)
Biomethane gas which has been applied as a renewable energy source in some of the industries, like automotive, food manufacturing, aerospace, and maritime, is regarded as the engine block of the economic advancement of most of the developed and developing countries. Hence, there is need to continuously explore the behavior of the energy source and to assess its performance when applied in some key engines and systems used in the different industries. In this paper, however, an integrated multicriteria-based model termed “triangular intuitionistic fuzzy hamming distance (TIFHD)” has been proposed for the performance evaluation of the biomethane gas as an energy source used for a specific system and engines with respect to the following criteria, environmental factor (CE), economic (CEc), social (CS), energy balance (CEb), and energy sustainability (CEs). The performance ranking results from the evaluation shows the following ranking order EN2 > EN1> EN3> EN4,with Stirling engine (EN4) and diesel-cycle engine (EN2) as the system and engines with the best and least biomethane gas performance respectively. EN1 and EN3 are industrial oven and the Otto cycle engine (gas motors) that is normally used in the food manufacturing and automotive industries, respectively